2021
DOI: 10.33830/jmst.v22i1.1490.2021
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Struktur Biaya Usaha Tani Bawang Merah Berdasarkan Tujuan Pasar Menggunakan Metode Cobb-Douglas Stochastic Frontier Production Function

Abstract: Shallots (Allium ascolonicum, L) are high-value horticultural commodities that need to be developed as strategic commodities in addition to rice, red chilies, chicken and beef. In addition, shallots have a high economic value and are a commodity used in the processing of various foods. This causes the consumption or demand for shallots to increase along with the increase in population. Therefore, this study aims to analyze the cost structure of shallot farming with the aim of the market for consumption and for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…Meanwhile, Razzianto et al [28] found the number of IDR 23,116,674.71 for the fried onion industry and IDR 44,242,628.19 for consumption.…”
Section: Total Cost Of Shallot Farming and Maximum Indemnitymentioning
confidence: 99%
“…Meanwhile, Razzianto et al [28] found the number of IDR 23,116,674.71 for the fried onion industry and IDR 44,242,628.19 for consumption.…”
Section: Total Cost Of Shallot Farming and Maximum Indemnitymentioning
confidence: 99%
“…Pemanfaatan faktor produksi dengan proses mengubah input menjadi output agar dapat digambarkan pada produksi padi agar memiliki produktivitas yang efisien dan efektif (Park, 2021). Fungsi produksi sebagai fungsi persamaan matematik yang melibatkan jumlah penggunaan input dan jumlah output, dalam kasus ini menggunakan dua atau lebih variabel Independen (X) dan Dependen (Y) (Karmini, 2018;Razzianto et al, 2021). Analisis regresi fungsi produksi Cobb Douglas digunakan untuk mengetahui pengaruh faktor apa yang mempengaruhi produksi padi (Bantaika, 2017;Musaba & Mukwalikuli, 2019).…”
Section: Pendahuluanunclassified